Solvatochromic CuII‐Containing Ionic Liquids with Ether Side Chains: Control of Solvent Response through Intramolecular Coordination. Issue 17 (13th April 2016) - Lan, Xue; Hosokawa, Hitoshi; Funasako, Yusuke; Mochida, Tomoyuki
Abstract : We reported previously that ionic liquids containing cationic solvatochromic metal–chelate complexes exhibit vapochromic and solvatochromic properties, changing color upon coordination of different solvents. To control the solvent response by intramolecular coordination, an ether side chain was introduced into the cation as an additional flexible coordination site, and ionic liquids of the formula [Cu(acac)Me2 NCH2 CH2 NMe(CH2 ) n OMe][Tf2 N] [1 ][Tf2 N]: n = 3, [2 ][Tf2 N]: n = 4; acac = acetylacetonato, Tf2 N = (F3 CSO2 )2 N – were synthesized. The melting points of [1 ][Tf2 N] and [2 ][Tf2 N] were 44.1 °C and 49.8 °C, respectively. X‐ray crystal‐structure determination revealed intramolecular coordination of the side chain in [1 ][Tf2 N] and its absence in [2 ][Tf2 N] in the solid state. The addition of 1 and 2 mol‐equiv. of dimethyl sulfoxide to [1 ][Tf2 N] produced ionic liquids with T m = 28.6 °C and –12.0 °C, respectively. To investigate the potential competition between side‐chain coordination and solvent coordination, the solvatochromism of these salts was investigated in various solvents. Although the d–d transition energy of [2 ][Tf2 N] varies linearly with the donor number ( DN ) of a solvent, that of [1 ][Tf2 N] is nearly constant in solvents with a DN smaller than that of methanol owing to intramolecular coordination. This demonstrates the control of solvent response by intramolecular coordination sites. Abstract : Ionic liquids containing solvatochromic metal–chelate complexes with a flexible ether side chain have been synthesized. These salts exhibit vapochromic and solvatochromic properties. The side‐chain coordination is released when solvents with coordination abilities stronger than that of the ether side chain are added.